The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1093/eurheartj/ehy452
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of complications related to catheter ablation of atrial fibrillation and atrial flutter: a nationwide in-hospital analysis of administrative data for Germany in 2014

Abstract: AimsRisks of catheter ablation for atrial fibrillation and flutter assessed in retrospective studies, registries, and controlled trials may underestimate ‘real world’ conditions.Methods and resultsTo assess complications in a nationwide approach, we included all cases undergoing catheter ablation for atrial fibrillation and atrial flutter in Germany in 2014, using ICD-10-GM-based German Diagnosis Related Group (G-DRG) codes and the well differentiated German Operation and Procedure Classification (OPS) analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 33 publications
7
86
1
9
Order By: Relevance
“…Although prior evaluations of the incidence of major AEs in AF patients who underwent CA included a low proportion of patients with comorbid HF (0.4% to 18%), the incidence of major AEs between 1% and 6% did not differ from the present study which only included patients with comorbid HF . Only two studies indicated that HF was a predictor for major AEs (univariate HR 5.2 [95% CI, 2.0‐13.4]); however, the comparable incidence between the present study and the safety evaluations of all AF patients undergoing CA seems to indicate no increase in AE risk with the addition of HF.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Although prior evaluations of the incidence of major AEs in AF patients who underwent CA included a low proportion of patients with comorbid HF (0.4% to 18%), the incidence of major AEs between 1% and 6% did not differ from the present study which only included patients with comorbid HF . Only two studies indicated that HF was a predictor for major AEs (univariate HR 5.2 [95% CI, 2.0‐13.4]); however, the comparable incidence between the present study and the safety evaluations of all AF patients undergoing CA seems to indicate no increase in AE risk with the addition of HF.…”
Section: Discussioncontrasting
confidence: 81%
“…Although prior evaluations of the incidence of major AEs in AF patients who underwent CA included a low proportion of patients with comorbid HF (0.4% to 18%), the incidence of major AEs between 1% and 6% did not differ from the present study which only included patients with comorbid HF. 1,6,7,[10][11][12][13][14][15][16][17][18][19]36 Only two studies indicated that HF was a predictor for major AEs The ROCKET-AF 37 and ARISTOTLE 38 trials have identified the chronic obstructive pulmonary disorder as a predictor of all-cause mortality in the AF population. In addition, HAS-BLED risk score has been identified as a predictor of long-term adverse outcomes, including mortality, in the AF population as well as other cardiovascular diseases and postcardiac procedures.…”
Section: Major Aes In Af Patients Undergoing Ca With or Without Commentioning
confidence: 99%
“…There were no significant adverse outcomes in either group in the present study except three patients with PCIS, while some significant adverse outcomes may occur after the procedure, such as sepsis, stroke and multiorgan failure. [15][16][17] Patients with delayed drain removal would have the propensity for enhanced inflammation reaction and a risk of infection, which would increase the possibility of those significant adverse outcomes. Early drain removal ultimately led to a quicker recovery with a significantly shorter hospital stay and high-quality, cost-effective care.…”
mentioning
confidence: 99%
“…Apart from AF recurrence, according to the available real‐world data, around 5%‐15% of patients undergoing AF catheter ablation experience complications, mainly during the index hospitalization and early in the post‐procedure course 320–325 . A variety of complications, including neurological, gastrointestinal, cardiovascular, vascular and peripheral, as well as pulmonary complications have been reported to occur after ablation procedures 320–325,343–347 . Although different modifiable factors such as metabolic syndrome, hypertension, alcohol consumption, sleep apnoea, and obesity have been proposed to be related with arrhythmia‐free survival after catheter ablation, 348–351 their impact on the ablation adverse outcomes is not clear yet, and requires further investigations.…”
Section: How To Assess Risk For Adverse Outcomes In Patients With Atrmentioning
confidence: 99%